In vitro activity and mode of action of phenolic compounds on Leishmania donovani - Antwi, C.A.; Amisigo, C.M.; Adjimani, J.P.; Gwira, T.M. (PLoS Neglected Tropical Diseases, 2019)
Background Leishmaniasis is a disease caused by the protozoan parasite, Leishmania. The disease remains a global threat to public health requiring effective chemotherapy for control and treatment. In this study, the effect of some selected phenolic compounds on Leishmania donovani was investigated. The compounds were screened for their anti-leishmanial activities against promastigote and intracellular amastigote forms of Leishmania donovani. Methodology/Principal findings The dose dependent effect and cytotoxicity of the compounds were determined by the MTT assay. Flow cytometry was used to determine the effect of the compounds on the cell cycle. Parasite morphological analysis was done by microscopy and growth kinetic studies were conducted by culturing cells and counting at 24 hours intervals over 120 hours. The cellular levels of iron in promastigotes treated with compounds was determined by atomic absorption spectroscopy and the effect of compounds on the expression of iron dependent enzymes was investigated using RT-qPCR. The IC50 of the compounds ranged from 16.34 μM to 124 μM compared to amphotericin B and deferoxamine controls. Rosmarinic acid and apigenin were the most effective against the promastigote and the intracellular amastigote forms. Selectivity indexes (SI) of rosmarinic acid and apigenin were 15.03 and 10.45 respectively for promastigotes while the SI of 12.78 and 5.20 respectively was obtained for intracellular amastigotes. Morphologically, 70% of rosmarinic acid treated promastigotes showed rounded morphology similar to the deferoxamine control. About 30% of cells treated with apigenin showed distorted cell membrane. Rosmarinic acid and apigenin induced cell arrest in the G0/G1 phase in promastigotes. Elevated intracellular iron levels were observed in promastigotes when parasites were treated with rosmarinic acid and this correlated with the level of expression of iron dependent genes. Conclusions/Significance The data suggests that rosmarinic acid exerts its anti-leishmanial effect via iron chelation resulting in variable morphological changes and cell cycle arrest.